Proactive data routing using controlled mobility of a mobile sink in Wireless Sensor Networks. (August 2018) - Mitra, Ratijit; Sharma, Suraj
Abstract: Stationary sink based Wireless Sensor Networks (WSN) have issues like sink neighborhood problem, end-to-end delay, data delivery ratio, network lifetime, etc. Although several routing approaches with mobile sink have been introduced to mitigate those issues across the network, very few, have considered delay requirements of applications. In this paper, we propose an efficient virtual grid based hierarchical routing approach suitable for delay bound applications, which judiciously selects a mobile sink's path by considering both hop counts and data generation rates of the sensor nodes, which reduces the overall energy consumption for multi-hop data communication. Data aggregation at each level of the hierarchy aims to reduce data traffic and increase throughput. The performance of the proposed protocol has been evaluated using simulation based on different metrics and compared with an existing routing protocol. Results have demonstrated that it performs better than the existing one while it still meets delay constraints of applications.